Evaluation of noise when a disturbing sound source cannot be off. (October 2016) - Trematerra, Amelia
This article shows the results of a method of acoustic measurements performed when a disturbing sound source cannot be turned off. This case happens when it is not possible accessing to disturbing sound source that we want to characterize, or when it cannot be switched off for reasons linked to production cycle. It is possible to carry out acoustic measurement of residual noise (noise present when disturbing source is off) with the technique of acoustically similar place. The residual noise in a certain area is a result of noise level emitted from various sound sources operating with a certain typicality in a considered area. This noise is going to be combined with noise of disturbing sound source, in place where complaints show up. If it is not possible to control disturbing sound source, residual noise surveys may be carried out in a similar place, or in a place where an environmental noise is equal and the influence of disturbing sound source is negligible.